2021
DOI: 10.1002/tox.23123
|View full text |Cite
|
Sign up to set email alerts
|

Sinapic acid mitigates methotrexate‐induced hepatic injuries in rats through modulation of Nrf‐2/HO‐1 signaling

Abstract: The present research has been investigated to study the protective outcomes of sinapic acid (SA) against methotrexate (MTX) encouraged liver damage in rats by modulating the Nrf2/HO‐1 and NF‐κB signaling pathways. The animals were arbitrarily allocated into four groups: group I rats administered a 0.5% carboxymethyl cellulose (CMC) vehicle orally for 15 consecutive days with a single intravenous standard saline injection (0.9% NaCl) on day seven. Groups II, III, and IV were injected intraperitoneally with 20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Sinapic acid (SA) is a hydroxycinnamic acid derivative that has been proven to have protective effects on different disease models, such as liver injury ( 8 ), hepatitis ( 9 ), nephrotoxicity ( 10 , 11 ), gastric ulcer ( 12 ), lung fibrosis ( 13 ) and epilepsy ( 14 ). An increasing number of studies have also found that SA exerts a cardioprotective effect.…”
Section: Introductionmentioning
confidence: 99%
“…Sinapic acid (SA) is a hydroxycinnamic acid derivative that has been proven to have protective effects on different disease models, such as liver injury ( 8 ), hepatitis ( 9 ), nephrotoxicity ( 10 , 11 ), gastric ulcer ( 12 ), lung fibrosis ( 13 ) and epilepsy ( 14 ). An increasing number of studies have also found that SA exerts a cardioprotective effect.…”
Section: Introductionmentioning
confidence: 99%
“…D-Gal administration causes the release of reactive oxygen species (ROS), which damage liver tissues [36,59,69]. It is clearly demonstrated here the potential of effect of D-Gal to induce oxidative stress in the liver as evidenced by elevated levels of oxidative stress by MDA and MPO and a significant decline in the antioxidant defences by SOD, CAT and GSH [4,12,21] These results are concurrent with the results of Zeweil et al, [67] and Balkan et al, [13]. Conversely, the pre-treatment with camel's milk and urine maintained the plasma levels of MDA, SOD, CAT, MPO and GSH within normal ranges, which could be attributed to the presence of bioactive constituents in camel's milk and urine with powerful radical scavenging activity.…”
Section: Resultsmentioning
confidence: 98%
“…On the one hand, sinapic acid ( 2 ) in SS inhibits bromodomain containing 4 (BRD4) expression and suppresses oxidative stress, cell scorching and hepatocyte injury ( Chu et al, 2021 ). On the other hand, SS can prevent methotrexate (MTX)-induced liver injury by inhibiting apoptosis and stimulating Nrf2/HO-1-intermediate antioxidant enzymes through NF-κB inhibition ( Ahmad et al, 2021 ). Sinapine ( 1 ) modulate the composition of intestinal flora, induce a decrease in the ratio of thick-walled phylum and mimic phylum, and increase the abundance of probiotic bacteria, thereby inhibiting hepatic steatosis ( Li et al, 2019 ).…”
Section: Pharmacologymentioning
confidence: 99%